PROPOSALS FOR IMPROVING THE PROCESS OF FORMING PROGRAMS OF REFORMING THE RAILWAY TRANSPORT INDUSTRY - A. M. Okorokov; M. O. Bulakh (Nauka ta progres transportu, 2018)
Purpose. The purpose of the work is to develop proposals for improving the process of forming measures and programs for reforming the railway transport industry of Ukraine in the process of European integration based on research, comparison and generalization of information. Methodology. A study of the content and the main provisions of legal acts declaring the conditions for the reform of the railway transport was carried out using analysis and synthesis methods. Methods of the system approach, comparison and generalization of the obtained data allowed developing proposals for improving the process of the formation of activities and programs. Findings. The need for reforming Ukraine's railway transport has been under consideration since 2006, but for a long time reform was limited only to the development of reforming plans and programs. Not being implemented within the framework of one program, the measures were reflected in the next or parallel one, with the corresponding change in the terms. The carried out analysis of their implementation does not allow talking about inactivity or denying the existence of positive changes, however, given the duration of the period 2006-2017, they occur very slowly. This situation requires new approaches to the development of programs and activities, as well as assessing their implementation, one of which is proposed in the work. Originality. The work justifies the need to evaluate the implementation of measures and programs for reforming the railway transport industry by two criteria: legal and practical. The developed basic principles for the formation of programs for reforming and developing the railway transport industry provide an opportunity to receive timely and reliable information on the status of their implementation. Practical value. We obtained the possibilities of constant monitoring of the state of financial support for reforms and directions of use of funds, which will prevent their misuse and significantly accelerate the implementation of certain activities, and then increase their effectiveness.